Lectures on Quantum Field Theory - Hořejší, Jiří (Karolinum, 2024)
The book covers the material of the two-semester course of quantum field theory that the author taught at Charles University and Czech Technical University in Prague for more than two decades. In the individual chapters one may find discussion of selected topics in relativistic quantum mechanics and relativistic quantum field theory; the dominant theme is quantum electrodynamics. The technique of Feynman diagrams is described in detail, as well as methods of regularization and renormalization, including some basic applications. The selection of the topics presented in the book is intended to provide the reader with the technical skills necessary for a subsequent study of theoretical particle physics. The text contains a lot of detailed explicit calculations in an extent not quite common in other available sources and this corresponds to the contents of the author's lectures. The readership is supposed to consist primarily of university students specializing in theoretical physics or nuclear and particle physics, but the publication may also be useful to any scientifically-minded reader seriously interested in the foundations of modern physics.
Keywords: Přírodní vědy